2020
DOI: 10.1088/1361-6528/ab8a8a
|View full text |Cite
|
Sign up to set email alerts
|

Dual-targeted therapy in HER2-positive breast cancer cells with the combination of carbon dots/HER3 siRNA and trastuzumab

Abstract: Dual -targeted therapy in HER2-positive breast cancer cells with the combination of carbon dots/HER3 siRNA and trastuzumab resulted in enhanced antitumor activity, which overcomes the resistance to trastuzumab monotherapy. Herein, we have developed branched polyethylenimine -functionalized carbon dot (BP-CD) nanocarriers, which exhibited efficient green fluorescent protein gene delivery and expression. The positively charged BP-CDs allowed for effective nucleic acid binding and displayed a high ly efficient sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…To study whether trastuzumab, an anti-HER2 monoclonal antibody, could improve the antitumour activity of equivalent amounts of adriamycin loaded on ChrGO, BT-474 cells were treated with trastuzumab alone or in combination with ChrGO/adriamycin. Treatment with trastuzumab alone produced a significant inhibition of BT-474 proliferation, which is consistent with a previous report [52]. The combined therapy with trastuzumab and ChrGO/adriamycin resulted in an enhanced cell growth inhibition effect, as shown by a reduction of 88.5% compared with a reduction of 54.5% with trastuzumab alone (5 μg/mL) and 59.5% with equivalent ChrGO/adriamycin alone (5 μg/mL) versus the negative control (Fig.…”
Section: Therapeutic Efficacy Of Chrgo/adriamycin Complexessupporting
confidence: 91%
“…To study whether trastuzumab, an anti-HER2 monoclonal antibody, could improve the antitumour activity of equivalent amounts of adriamycin loaded on ChrGO, BT-474 cells were treated with trastuzumab alone or in combination with ChrGO/adriamycin. Treatment with trastuzumab alone produced a significant inhibition of BT-474 proliferation, which is consistent with a previous report [52]. The combined therapy with trastuzumab and ChrGO/adriamycin resulted in an enhanced cell growth inhibition effect, as shown by a reduction of 88.5% compared with a reduction of 54.5% with trastuzumab alone (5 μg/mL) and 59.5% with equivalent ChrGO/adriamycin alone (5 μg/mL) versus the negative control (Fig.…”
Section: Therapeutic Efficacy Of Chrgo/adriamycin Complexessupporting
confidence: 91%
“…These results suggested that the surface passivation by PEI imparted a strong influence on the optical properties of N-CDs due to a change in the chemical functional groups. 47 Furthermore, the time-resolved fluorescence spectrum measured with an excitation at 350 nm showed that the fluorescence lifetime of N-CDs is 3.35 ns ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average hydrodynamic size of the BP-NCDs measured by DLS was 42.1 nm, which was slightly larger than that of the bare N-CDs (30.4 nm) due to the presence of the polymer PEI envelope ( Figure 2E ). 47 The surface charge of BP-NCDs reflects the capability of cationic-related carriers for nucleic acid delivery. 43 Zeta potential analysis demonstrated that the surface charge of N-CDs, branch PEI, and BP-NCDs was 7 mV, 10 mV, and 18 mV, respectively ( Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations